Kinetics of the sulfur oxidation on palladium: A combined in situ x-ray photoelectron spectroscopy and density-functional study - Gotterbarm, Karin; Luckas, Nicola; Höfert, Oliver; Lorenz, Michael Peter Andreas; Streber, Regine; Papp, Christian; Vines, Francesc; Steinrück, Hans-Peter; Görling, Andreas (Journal of Chemical Physics, 2012)
We studied the reaction kinetics of sulfur oxidation on the Pd(100) surface by in situ high resolution x-ray photoelectron spectroscopy and ab initio density functional calculations. Isothermal oxidation experiments were performed between 400 and 500 K for small amounts (∼0.02 ML) of preadsorbed sulfur, with oxygen in large excess. The main stable reaction intermediate found on the surface is SO , with SO and SO being only present in minor amounts. Density-functional calculations depict a reaction energy profile, which explains the sequential formation of SO , SO , and eventually SO , also highlighting that the in-plane formation of SO from S and O adatoms is the rate limiting step. From the experiments we determined the activation energy of the rate limiting step to be 85 6 kJ mol by Arrhenius analysis, matching the calculated endothermicity of the SO formation. © 2012 American Institute of Physics.